SUMOylation of Translationally Regulated Tumor Protein Modulates Its Immune Function - Lu, Chenchen; Li, Zhiqing; Zhang, Wenchang; Guo, Hao; Lan, Weiqun; Shen, Guanwang; Xia, Qingyou; Zhao, Ping (Frontiers in Immunology, 2022)
Translationally controlled tumor protein (TCTP) is a highly conserved protein possessing numerous biological functions and molecular interactions, ranging from cell growth to immune responses. However, the molecular mechanism by which TCTP regulate immune function is largely unknown. Here, we found that knockdown of Bombyx mori TCTP (BmTCTP) led to the increased susceptibility of silkworm cells to virus infection, whereas overexpression of BmTCTP significantly decreased the virus replication. We further demonstrated that BmTCTP could be modified by SUMOylation molecular BmSMT3 at the lysine 164 via the conjugating enzyme BmUBC9, and the stable SUMOylation of BmTCTP by expressing BmTCTP-BmSMT3 fusion protein exhibited strong antiviral activity, which confirmed that the SUMOylation of BmTCTP would contribute to its immune responses. Further work indicated that BmTCTP is able to physically interact with interleukin enhancer binding factor (ILF), one immune molecular, involved in antivirus, and also induce the expression of BmILF in response to virus infection, which in turn enhanced antiviral activity of BmTCTP. Altogether, our present study has provided a novel insight into defensing virus via BmTCTP SUMOylation signaling pathway and interacting with key immune molecular in silkworm.